Seismic response of non-linear base-isolated shear buildings and their secondary systems - Cui, Wei. (2009)
Base isolation has been proven to be one of the most effective techniques to provide protection for both buildings and their contents during earthquake and has gained increasing acceptance in the past two decades. The successful seismic isolation of a particular building depends strongly on the selection of an appropriate base isolation system. Therefore, it is very important to have a deep understanding of the influence of each parameter in the isolation system and the superstructure on the seismic performance of both the isolated buildings and their contents.